Ophthalmology Encounters During the COVID-19 Pandemic in a Student Run Free Clinic - Anindya Samanta; Alexander Park; Kelly Mitchell (Journal of Student-Run Clinics, 2024)
Background: Ophthalmology services at student run free clinics (SRFC) serve an important role for the socioeconomically underserved within a city. The coronavirus disease 2019 (COVID-19) pandemic has worsened gaps in care for ophthalmology tertiary clinics, but its effects on ophthalmology encounters at SRFCs are not known.Methods: This was a retrospective chart review from a single center that compared patient encounters in the ophthalmology SRFC six months prior to its closure (pre-COVID group) with patient encounters in the ophthalmology SRFC six months after its reopening (post-COVID closure group).Results: There was a decline (47.3%) in the number of encounters in the post-COVID closure group (n=20) when compared to the pre-COVID group (n=38). While the number of encounters for routine screening stayed about the same in both groups, there was a 90.5% decline in encounters with active disease (21 pre-COVID vs. 2 post-COVID closure). Sub-group analysis of the pre-COVID group showed that patients with active disease tended to have worse vision (-0.33 logMAR, p=0.034 OD; -0.27 logMAR, p=0.048 OS) than those undergoing routine screening.Conclusions: Patients in West Texas with active eye diseases are not presenting to SRFC after its reopening. Early recognition of this is critical to address the potential gap in care in a vulnerable population.